Can Health Systems Platforms Do More for Nutrition in India? Insights on Missed Opportunities from India's National Family Health Survey, 2015–2016. (29th May 2020) - Nguyen, Phuong; Menon, Purnima; Avula, Rasmi; Tran, Lan Mai; Kumar, Alok; Baswal, Dinesh; Sethi, Vani; Hajeebhoy, Nemat; Ranjan, Alok
Abstract: Objectives: Most nutrition interventions can be delivered through health systems. However, the progress to scale up effective nutrition interventions and achieve universal health coverage has not been uniform. We aimed to 1) examine the opportunity gaps (OGs) between delivery platforms and corresponding nutrition interventions through the continuum of care (from pregnancy up to early childhood) in India between 2006 and 2016; and 2) assess inequalities in these OGs. Methods: We used two rounds of National Family Health Survey data collected in 2005–06 and 2015–16 ( n = 36, 850 and 190, 898 mother-child dyads with the last child aged of 0–5 years, respectively). We examine the OGs over time for a set of seven nutrition interventions and their associated delivery platforms during antenatal, delivery, postnatal and early childhood care at the national, state and district levels. We then assessed equality and changes in equality between 2006–2016 for the OGs by education, residence, socioeconomic status, public and private platforms. Results: Coverage of nutrition interventions was consistently lower than the reach of their associated delivery platforms, with the OGs ranging from 9–32 percentage points (pp) during pregnancy, 17pp during delivery, and 9–26pp during childhood in 2006. Between 2006 and 2016, coverage improved for most indicators but the OGs became wider. The OGs were larger among women with higher education, higher SES status and living in urban areas, despite higher coverage of most interventions and the delivery platforms among these groups. Compared to private facilities, public facilities performed better in counseling/support for breastfeeding but were poorer in iron and folic acid supplementation. OGs vary tremendously by state and district, highlighting governance and implementation successes and challenges. Conclusions: India's progress in coverage of health and nutrition interventions in the last decade is promising, but both opportunity and equity gaps must be closed by addressing policy and programmatic health systems bottlenecks to achieve universal coverage for both health and nutrition. We recommend this analytic approach to track and assess OGs in scaling up nutrition through health systems in India and worldwide. Funding Sources: Bill & Melinda Gates Foundation through POSHAN, led by IFPRI.